Hybrid Leadership as a Balancing Act - Qualitative Insights from a Financial Institution - Schwehn, Tim-Julian; Meier, Florian; Laumer, Sven (Hawaii International Conference on System Sciences (HICSS), 2025)
We explore the challenges and dynamics of hybrid leadership in organizations transitioning from traditional on-site to hybrid work environments. Using a qualitative single case study approach, we conducted 23 semi-structured interviews with hybrid leaders and employees at a financial institution. Our findings reveal three core paradoxes: ‘change vs. normality’, ‘digital connectivity vs. digital separation’, and ‘trust boosting vs. trust challenging’. These paradoxes highlight the complex balance hybrid leaders must achieve between leveraging technology for efficiency and maintaining interpersonal connections and trust. We propose that hybrid leadership requires new skills and strategies to navigate these tensions effectively. The study contributes to theory and practice by highlighting how the three identified paradoxes impact hybrid work and hybrid leadership. Our findings underscore the importance of adopting both/and approaches to address the presented paradoxes of hybrid leadership in hybrid wor
Keywords: hybrid leadership; hybrid work; paradox theory; e-leadership; virtual leadership